Medical narrative competency, empathy, and self-efficacy among senior medical undergraduates in China: a cross-sectional analysis - Fang Liu; Shangqin Liu; Lijing Xia; Rui Pang; Hengyu Zhou (BMC Medical Education)
Abstract Background Medical students’ narrative competence plays a pivotal role in ensuring the future quality of medical services. Identifying the variables associated with narrative competence may be instrumental in preparing to improve medical undergraduates’ narrative competence. Objectives This study aimed to investigate the current status and influencing factors affecting medical students’ narrative competency while exploring the correlations among self-efficacy, empathy, and medical narrative competence. Methods This study employed a quantitative cross-sectional design and enrolled 434 full-time senior medical undergraduates at a university in Chongqing, China, through convenience sampling. Medical undergraduates who met the inclusion criteria completed an online survey using self-report scales for self-efficacy, empathy, and medical narrative competence between October and November 2023. Multivariate linear regression analysis was performed to explore the influencing factors. Results Medical students scored 137.03 ± 16.42 on narrative competency, 25.84 ± 5.40 on self-efficacy, and 51.04 ± 11.93 on empathy. Narrative competency was positively correlated with self-efficacy (r = 0.345, p < 0.01) and empathy (r = 0.492, p < 0.01). Multiple linear regression analysis revealed that the final model adopted was statistically significant (F = 18.203; p < 0.001; R2 = 0.342). Main factors influencing narrative competency included students’ majors, the role of student leaders, empathy levels, and self-efficacy (p < 0.05), explaining 34.2% of the total variation. Conclusion Empathy and self-efficacy are closely associated with narrative competencies in medical undergraduates. Therefore, educational activities that prioritize the cultivation of empathy and self-efficacy may serve as an alternative approach for enhancing narrative competency among Chinese medical undergraduates.